Phytochemistry, pharmacological properties, and recent applications of Ficus benghalensis and Ficus religiosa - Murugesu, Suganya; Selamat, Jinap; Perumal, Vikneswari (Multidisciplinary Digital Publishing Institute, 2021)
Ficus is one of the largest genera in the plant kingdom that belongs to the Moraceae family. This review aimed to summarize the medicinal uses, phytochemistry, and pharmacological actions of two major species from this genus, namely Ficus benghalensis and Ficus religiosa. These species can be found abundantly in most Asian countries, including Malaysia. The chemical analysis report has shown that Ficus species contained a wide range of phytoconstituents, including phenols, flavonoids, alkaloids, tannins, saponins, terpenoids, glycosides, sugar, protein, essential and volatile oils, and steroids. Existing studies on the pharmacological functions have revealed that the observed Ficus species possessed a broad range of biological properties, including antioxidants, antidiabetic, anti-inflammatory, anticancer, antitumor and antiproliferative, antimutagenic, antimicrobial, anti-helminthic, hepatoprotective, wound healing, anticoagulant, immunomodulatory activities, antistress, toxicity studies, and mosquitocidal effects. Apart from the plant parts and their extracts, the endophytes residing in these host plants were discussed as well. This study also includes the recent applications of the Ficus species and their plant parts, mainly in the nanotechnology field. Various search engines and databases were used to obtain the scientific findings, including Google Scholar, ScienceDirect, PMC, Research Gate, and Scopus. Overall, the review discusses the therapeutic potentials discovered in recent times and highlights the research gaps for prospective research work.